URGENSI PENGAMALAN ILMU PENGETAHUAN YANG MULIA DI TENGAH ERA REVOLUSI INDUSTRI 4.0 DALAM PERSPEKTIF HINDU - Darma Permana, I Dewa Gede (Satya Widya: Jurnal Studi Agama, 2023)
Abstract The arrival of the industrial revolution 4.0 era brought major changes to technological developments. This then leads to the positive and negative impacts of technology in every area of life, including the development of science. Reflecting on this, this research is interested in studying in more depth about the urgency of noble science amid the industrial revolution 4.0 era from a Hindu perspective. To support this goal, this research formulates several problems, namely related to the nature of science according to Hinduism, the nature of the industrial revolution 4.0 and its impact on the development of science, and finally formulating the urgency of practicing noble science in the era of the industrial revolution 4.0 in a Hindu perspective. By using qualitative research methods, literature studies, and using data analysis from Miles and Huberman. The results of this study indicate that the practice of noble knowledge is something important in the era of the industrial revolution 4.0, as an antidote to false information through the teachings of Tri Pramana, and achieving a balance of knowledge through the teachings of Jnana Marga Yoga.